Using the concept of preperitoneal membrane anatomy in total extraperitoneal prosthesis: a preliminary report - Lin, Suqiong; Hu, Anran; Zheng, Huabin; Fu, Jinbo; Kuang, Penghao; Hong, Xiaoquan; Qiu, Rongliang; Fu, Yilong (Frontiers in Surgery, 2023)
PPurpose: Total extraperitoneal prosthesis (TEP) is currently one of the most commonly used laparoscopic inguinal hernia repair procedures. This work aims to report the application of membrane anatomy to TEP and its value in intraoperative space expansion. Methods: The clinical data of 105 patients, from January 2018 to May 2020, with inguinal hernia who were treated with TEP (58 patients in the General Department of the Second Hospital of Sanming City, Fujian Province and 57 patients in the General Department of the Zhongshan Hospital Affiliated to Xiamen University) were retrospectively analyzed. Results: All surgeries were successfully completed under the guidance of the concept of preperitoneal membrane anatomy. The operation time was (27.5 ±9.0) min, the blood loss was (5.2 ± 0.8) mL, and the peritoneum was damaged in 6 cases. The postoperative hospital stay was (1.5 ± 0.6) day and 5 cases of postoperative seroma occurred, all of which were self-absorbed. During the follow-up period of 7 to 59 months, there was no case of chronic pain and no recurrence. Conclusion: The membrane anatomy in the correct level is the premise of bloodless operation, so as to expand the space while protecting adjacent tissues and organs to avoid complications.